Blood immunomap for prediction of responses to anti-PD-1 immunotherapy in metastatic non-small cell lung cancer - Maria Semitekolou; Nikolaos Paschalidis; Domenico Lo Tartaro; Aikaterini Tsitsopoulou; Panagiota Stamou; Alexandros Mavroudis; Effrosyni Markaki; Athina Varveri; Ioannis Morianos; Matthieu Lavigne; Charalampos Fotsitzoudis; Sofia Magkouta; et al. (iScience)
Summary: The identification of circulating predictors of response to ICB therapy is vital as very few of them meet the demands of the clinic. Herein, by using high-dimensionality mass cytometry, we designed a blood immunomap in metastatic NSCLC individuals who underwent anti-PD-1 treatment. We identified heightened frequencies of CD8+PD-L1+ T cells in non-responders compared to responders. Notably, imaging mass cytometry data revealed that CD8+PD-L1+ T cells were enriched in tumor biopsies, pleural infusions, and BAL of early-stage NSCLC individuals, proposing this cells subset as candidate not only for the advanced but also for early disease detection. Transcriptomic analysis unveiled that CD8+PD-L1+ T cells displayed an exhausted phenotype related to their increased frequencies to non-responders to immunotherapy, and gene signatures correlated with the overall survival of an independent cohort. Overall, our study pinpoints immune-related events which may benefit the quest for detection of predictive biomarkers of immunotherapy responses.